The Social Relationship of Research in a Study about the Agency of Children in School-Family Interface - Zenhas, Armanda; Rocha, Cristina; Silva, Pedro (International Journal about Parents in Education, 2023)
The content of this paper is part of a broader research that took place in Portugal. It is related to children’s experience in school-family interface throughout the 5th grade, when an ecological transition occurs due to an educational stage transition. Our purpose is to examine the social relationship of research established between the researcher and the children, their parents and teachers, from the moment the students move into the new school. With the children's agency within the framework of school-family relationships as background, and having implemented a qualitative methodology, using the main tools of the ethnographic method, the data were collected with the children in weekly participatory activities and through conversational interviews. Data were also collected from teachers and parents, through interviews and through observation of weekly lessons with the class tutor and of parents’ meetings. The data collected were subjected to content analysis. This research reveals children as competent social actors who act intentionally and strategically in the school-family relationship structure. This strategic action is further reflected in the way children appropriate the data collection activities promoted with them. Moreover, it is also present in the strategic uses they make of the social relationship established with them.